2011
DOI: 10.1124/mol.110.070177
|View full text |Cite
|
Sign up to set email alerts
|

Helix 8 of the M1Muscarinic Acetylcholine Receptor: Scanning Mutagenesis Delineates a G Protein Recognition Site

Abstract: We have used alanine-scanning mutagenesis followed by functional expression and molecular modeling to analyze the roles of the 14 residues, Asn422 to Cys435, C-terminal to transmembrane (TM) helix 7 of the M 1 muscarinic acetylcholine receptor. The results suggest that they form an eighth (H8) helix, associated with the cytoplasmic surface of the cell membrane in the active state of the receptor. We suggest that the amide side chain of Asn422 may act as a cap to the C terminus of TM7, stabilizing its junction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…an appropriate antagonist. A similar pharmacological chaperone effect was also reported for helix 8-defective mutants of the leukotriene B4 type 2 receptor (17) and for the muscarinic M 1 receptor (14), implying a potential therapeutic approach to rescue respective defective receptors.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…an appropriate antagonist. A similar pharmacological chaperone effect was also reported for helix 8-defective mutants of the leukotriene B4 type 2 receptor (17) and for the muscarinic M 1 receptor (14), implying a potential therapeutic approach to rescue respective defective receptors.…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, helix 8 is an excellent candidate for the agonist-induced recognition of and interaction with cytosolic binding partners and has been studied extensively in several GPCRs. Studies have not only shown the involvement of helix 8 in G protein activation (11)(12)(13)(14)(15) but also identified hydrophobic residues in helix 8 as essential for the surface expression of the GPCRs investigated (11,16,17). In addition, it has been published only recently that mutation of positively charged residues in helix 8 of the thyrotropin releasing hormone receptor prevented GRK-mediated receptor phosphorylation (18).…”
mentioning
confidence: 99%
“…In fact, the H8 domain is critical for G protein coupling as observed for rhodopsin 23 and for other GPCRs (see 24 ). More interestingly, the H8 of the muscarinic M3R was shown to cross-link with the Gαq protein in an agonist-dependent manner 25 suggesting a close proximity between the receptor H8 domain and the G protein.…”
mentioning
confidence: 94%
“…This helical region has been shown to be involved in the G protein activation, trafficking and function of the receptors [32, 52, 53]. Highly concentrated, positively charged residues in helix 8 have been defined to be essential for the cell surface expression of some GPCRs [25].…”
Section: Discussionmentioning
confidence: 99%